2008
DOI: 10.1021/jp8037279
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Production with Visible Light over Pt-Interlinked Hybrid Composites of Cubic-Phase and Hexagonal-Phase CdS

Abstract: A hybrid photocatalytic system, which is based on a mixed-phase cadmium sulfide matrix composed of nanoparticulate cubic-phase CdS (c-CdS) with average particle diameters of 13 nm and a bandgap energy of 2.6 eV, is coupled with bulk-phase hexagonal CdS (hex-CdS) that has a bandgap energy of 2.3 eV and is interlinked with elemental platinum deposits. The resulting hybrid nanocomposite catalysts are photocatalytically efficient with respect to hydrogen gas production from water with visible light irradiation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(155 citation statements)
references
References 23 publications
9
140
0
6
Order By: Relevance
“…This means the appearance of the particles with cubic structure. 26 This result further confirms the formation of the nanorods with cubic crystal structure under long time ripening, consistent with the TEM, HRTEM and XRD investigations.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This means the appearance of the particles with cubic structure. 26 This result further confirms the formation of the nanorods with cubic crystal structure under long time ripening, consistent with the TEM, HRTEM and XRD investigations.…”
Section: Resultssupporting
confidence: 88%
“…These composite nano-particulate films are of great importance on their photocatalytic properties and applications. For example, Silva et al 26 used a hybrid system composed of nanoparticulate CdS with cubic zinc blende structure and bulk phase hexagonal CdS interlinked with Pt deposits as a photocatalyst to produce H2 from water under visible light irradiation. They found that the hybrid system has higher photocatalytic activity than other systems, such as the composites of CdS with pure crystal structure with Pt, and the CdS with hexagonal or cubic structure only.…”
mentioning
confidence: 99%
“…A synthesis medium with strong hydrogenbond basicity, for example, may lead to better stabilisation of the CdS crystallites with surface hydroxyl groups, which may follow a different photocatalytic pathway than the mechanism postulated above, which is based on the sulfide adsorption being the rate-determining step. [33] It is also possible that steric effects and solvent viscosity may reduce the frequency of the solvent-crystal intermolecular interactions that are required for the formation of the active surfaces. Further characterisation of these solvent-crystal interactions, which is currently being undertaken, will provide a more complete description of the manner in which crystal properties evolve within different solvent systems, and will build on the approach presented herein that allows for an increasingly more rational design of functional crystals.…”
Section: N T Value For the [Tba]a C H T U N G T R E N N U N G [Val] Smentioning
confidence: 99%
“…22,[27][28][29][30][31] Many works 26,[32][33][34][35][36][37] have shown that the photocatalytic degradation of organic compounds, such as azo dyes, proteins, alcohols, sugars, and organic acids, under non-aerated conditions takes place with the simultaneous production of hydrogen over irradiated semiconductor photocatalyst suspensions or immobilized films. Other strange sources of organic compounds have been investigated since the 1980s.…”
Section: Photoinduced Reformation Of Biomassmentioning
confidence: 99%